Multi-level governance of low-carbon tourism in rural China: policy evolution, implementation pathways, and socio-ecological impacts - Yi Guo; Shengchao Li (Frontiers in Environmental Science)
Low-carbon rural tourism development presents a critical challenge for environmental governance in emerging economies, yet the multi-level dynamics of policy implementation remain underexplored. This study examines China’s approach to this challenge, employing a mixed-methods approach including analysis of 16 central and 559 provincial policy documents, case studies in 15 rural villages across five provinces (Hunan, Guangdong, Zhejiang, Shanxi, and Hainan), and a survey of 637 stakeholders. Our findings reveal a complex policy landscape characterized by evolving national frameworks, varied provincial adoption patterns influenced by economic, environmental, and institutional factors, and three distinct local implementation pathways: technology-driven, community-based, and policy-led. We uncover significant variations in stakeholder perceptions and socio-economic impacts across different contexts, highlighting the critical role of adaptive governance mechanisms and local contextual factors in determining policy effectiveness. This study contributes to policy diffusion and multi-level governance theories by demonstrating the intricate interplay between top-down directives and bottom-up innovations in shaping sustainable tourism outcomes. Based on these insights, we propose evidence-based policy recommendations emphasizing flexible, context-sensitive approaches and improved stakeholder engagement to enhance low-carbon rural tourism governance. This research provides valuable guidance for policymakers and practitioners working towards sustainable rural development and environmental conservation in China and other developing countries.